2020
DOI: 10.21203/rs.3.rs-53518/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gut microbiome, a potential indicator for differential diagnosis of major depressive disorder and general anxiety disorder

Abstract: Background Major depressive disorder (MDD) and general anxiety disorder (GAD) share many common features, leading to many challenges in their differential diagnosis. Given the importance of the microbiota-gut-brain axis, we aimed to investigate the differences in gut microbiota between representative cases of these two diseases and sought to develop a microbiome-based approach for their differential diagnosis.Methods We enrolled 23 patients with MDD, 21 patients with GAD, and 10 healthy subjects (health contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…One study only investigated pathways associated with tryptophan metabolism and biosynthesis, identifying differences between cases and controls [75]. Another study observed correlations between specific bacterial taxa and functional pathways within the KEGG orthologue database; however, they did not report what the specific pathways were, only providing the KEGG identification number [88]. Of the studies that examined multiple pathways and reported differences (N = 9), MDD was associated with an enrichment of: glycan biosynthesis and metabolism (33%; N = 3/ 9 reported studies) [86,89]; lipopolysaccharide biosynthesis and biosynthesis proteins (33%; N = 3/9 reported studies) [72,85]; and transport and catabolism pathways (33%; N = 3/9 reported studies) [86,89], compared to controls.…”
Section: Functional Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…One study only investigated pathways associated with tryptophan metabolism and biosynthesis, identifying differences between cases and controls [75]. Another study observed correlations between specific bacterial taxa and functional pathways within the KEGG orthologue database; however, they did not report what the specific pathways were, only providing the KEGG identification number [88]. Of the studies that examined multiple pathways and reported differences (N = 9), MDD was associated with an enrichment of: glycan biosynthesis and metabolism (33%; N = 3/ 9 reported studies) [86,89]; lipopolysaccharide biosynthesis and biosynthesis proteins (33%; N = 3/9 reported studies) [72,85]; and transport and catabolism pathways (33%; N = 3/9 reported studies) [86,89], compared to controls.…”
Section: Functional Potentialmentioning
confidence: 99%
“…Of the studies that collected additional biomarker data (27%; N = 12/44 studies), immune-related and inflammatory markers, such as interleukin 6 and C-reactive protein, were the most commonly reported (58%; N = 7/12 reporting studies). Five studies conducted metabolomic analyses: two studies in MDD found no differences in faecal metabolites [74] or neuroendocrine hormones [88]; two studies observed differences in multiple faecal metabolites in MDD cases compared to controls, mainly related to amino acid, nucleotide, carbohydrate, and lipid metabolism [86], and inflammatory pathways [87]; and a fifth study in SZ observed differences in tryptophan and kynurenine pathway metabolites [106] (Table S5).…”
Section: Psychiatric Symptom Severity and Gut Microbiota Compositionmentioning
confidence: 99%